Analisis Strategi dan Potensi Usaha Kuliner Bubur Ayam: Studi Kasus: Usaha "Kaka Celin" di Maumere - Emilianus Eo Kutu Goo; Imelda Ndiki; Serafin Constatia Enjelita; Magdalena Grengan; Gabriela Christina; Christina Yovani Heret (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2026)
This study aims to analyze business strategies, operational processes, and challenges in running a chicken porridge culinary business in Maumere, focusing on the case of the “Kaka Celin” Chicken Porridge business. The research employs a qualitative approach using direct interviews with the business owner located at Kimang Buleng Street No. 3, Maumere. The collected data were analyzed descriptively to provide an overview of the implementation of strategic management practices in a small-scale culinary enterprise. The findings indicate that the success of the “Kaka Celin” business is influenced by several key factors, including its strategic location in front of a school and along a public traffic route, the uniqueness of its product in the form of chicken porridge served without broth, which is relatively uncommon in Maumere, and the use of social media as a promotional tool to reach a wider customer base. In terms of operations, the business sells an average of 70–90 portions of chicken porridge per day, generating an estimated daily net profit ranging from IDR 400,000 to IDR 500,000 from various menu combinations. The main challenge faced by the business is the need for strict time discipline, particularly the routine of waking up in the early morning hours to prepare production. Overall, this business demonstrates strong potential for sustainable development if the implemented strategies are managed consistently and effectively.